The impact of electricity supply in Malawi on Economic Development - Milanzi, S. A.; Daw, D. (International Conference on Public Administration and Development Alternatives, 2018)
The need for electrical infrastructure development in Malawi has to be revisited as the population growth and demand for electricity is increasing. In achieving the outcome of this study time series data from the year 1991-2014 has been used. In application of ARDL approach the results shows that load shading occurs periodically as results of high demand in electricity and low supply. It has been seen that the country has only few power generators which produce electricity in small quantity which does not meet the required demand. It has been seen that there might have been a long-run relationship between power utilization and GDP per capita in the country. The economy is mostly dependent on energy for manufacturing sector and other sectors to function productively and contribute to the economic growth. Keywords: Economy, Electricity, Growth, Infrastructure, Manufacturing
Journal Article Published in: The 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Economy; Electricity; Growth; Infrastructure; Manufacturing; Rural electrification